PENINGKATAN ACCOUNTABILITY FOR VILLAGE FUND MANAGEMENT MELALUI PENERAPAN INTERNAL CONTROL SYSTEM, VILLAGE GOVERNMENT COMPETENCE DAN SOCIETY PARTICIPATION (Studi Pada Desa Se-Kecamatan Cikupa Kabupaten Tangerang) - Sahrul, Veira Sylvia; Atichasari, Anna Sofia; Ristiyana, Rida (Universitas Islam Syekh-Yusuf, 2021)
This study aims to increase the accountability of village fund management through the application of a government internal control system, village government competence and society participation. The study population was all village governments in Cikupa sub-district, Tangerang Regency, Banten Province which consisted of 12 villages. The sampling method used purposive sampling which obtained 80 respondents and data analysis using multiple linear regression. The results found that the government internal control system and society participation had a positive significant effect on the accountability of village fund management and the competence of the village government did not affect on the accountability of village fund management Keywords: Accountability of Village Fund Management, Government Internal Control System, Village Government Competence, Society Participation